Cryotherapy in the treatment of glandular odontogenic cyst: case report and review (Revista da Faculdade de Odontologia - UPF, 2016)
Objective: The Glandular Odontogenic Cyst (GOC) isa rare benign odontogenic lesion, of considerable aggression,and often incorrectly diagnosed. We present apatient with a Glandular Odontogenic Cyst in the posteriormandible, its evolution, treatment, and follow-up.Case report: A female patient, 45 years old, was referredto the Oral and Maxillofacial Surgery and TraumatologyDivision at Cristo Redentor Hospital, Porto Alegre, Brazil,for the assessment of a painful edema on the righthemiface. A unilocular area with well-defined bordersin the retromolar region, posterior to the third molar onthe right side of the mandible. The histopathologicalexamination suggested GOC. Final considerations: TheGlandular Odontogenic Cyst needs a complete clinicalassessment associated with image analyses, and especially,with histopathology for the correct diagnosis ofthe lesion, since the diagnosis may be mistaken in clinicaland radiographic examination. There are several treatmentoptions; however, enucleation associated withcryotherapy, in this case, was an effective method forthe treatment of Glandular Odontogenic Cyst.